Anode for secondary battery, secondary battery including the same and method of preparing the same

KR103031105B1Active Publication Date: 2026-10-13SK ON CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
KR1020210107208
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-08-13
Publication Date
2026-10-13
Estimated Expiration
2041-08-13

Smart Images

  • Figure 112021093639232-PAT00001_ABST
    Figure 112021093639232-PAT00001_ABST
Patent Text Reader

Abstract

A negative electrode active material for a secondary battery according to exemplary embodiments comprises a first negative electrode active material particle in the form of a single particle, comprising a core particle and a coating layer formed on the surface of the core particle, and a second negative electrode active material particle in the form of a single particle, having an average particle size larger than that of the first negative electrode active material particle, wherein the content ratio of the first negative electrode active material relative to the total weight of the first negative electrode active material and the second negative electrode active material particle is greater than 50% by weight and less than 100% by weight. The stability of the first negative electrode active material particle is improved through the formation of the coating layer, and the capacity characteristics of the battery can be improved through the mixing of the first negative electrode active material particle and the second negative electrode active material particle.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a negative electrode for a secondary battery, a secondary battery comprising the same, and a method for manufacturing the same. More specifically, the invention relates to a negative electrode for a secondary battery comprising heterogeneous particles, a secondary battery comprising the same, and a method for manufacturing the same. Background Technology

[0002] Rechargeable batteries are batteries capable of repeated charging and discharging, and with the advancement of the information and communication and display industries, they have been widely applied in portable electronic communication devices such as camcorders, mobile phones, and laptop PCs. Examples of rechargeable batteries include lithium-ion batteries, nickel-cadmium batteries, and nickel-hydrogen batteries; among these, lithium-ion batteries have been actively developed and applied due to their high operating voltage and energy density per unit weight, as well as advantages in charging speed and weight reduction.

[0003] A lithium secondary battery may include, for example, an electrode assembly comprising a positive electrode, a negative electrode, and a separator, and an electrolyte impregnating the electrode assembly. The lithium secondary battery may further include, for example, an outer casing in the form of a pouch that accommodates the electrode assembly and the electrolyte.

[0004] For example, the above-mentioned cathode may use carbon-based or silicon-based active material particles as the cathode active material. When charging and discharging are repeated, side reactions may occur due to contact with the electrolyte, and mechanical or chemical damage, such as cracks in the particles, may occur.

[0005] If the composition and structure of the negative electrode active material are changed to improve the stability of the active material particles, conductivity may decrease, which may lead to a deterioration in the output of the secondary battery.

[0006] Therefore, it is necessary to develop cathode active materials capable of ensuring lifespan stability and output / capacity characteristics.

[0007] For example, Korean Patent Publication No. 2017-0099748 discloses an electrode assembly for a lithium secondary battery and a lithium secondary battery including the same. Prior art literature

[0008] Korean Patent Publication No. 10-2017-0099748 The problem to be solved

[0009] One objective of the present invention is to provide a negative electrode active material for a secondary battery having improved stability and activity.

[0010] One objective of the present invention is to provide a secondary battery having improved stability and activity.

[0011] One objective of the present invention is to provide a method for manufacturing a negative electrode active material for a secondary battery having improved stability and activity. means of solving the problem

[0012] A negative electrode for a secondary battery according to exemplary embodiments comprises a first negative active material particle in the form of a single particle, comprising a core particle and a coating layer formed on the surface of the core particle; and a second negative active material particle having an average particle size larger than that of the first negative active material particle, wherein the content ratio of the first negative active material is greater than 50 weight% and less than 100 weight% relative to the total weight of the first negative active material and the second negative active material particle.

[0013] In a negative electrode for a secondary battery according to some exemplary embodiments, the core particles may comprise a graphite-based active material, an amorphous carbon-based material, or a mixture of a graphite-based active material and an amorphous carbon-based material.

[0014] In a negative electrode for a secondary battery according to some exemplary embodiments, the core particles may include artificial graphite.

[0015] In a negative electrode for a secondary battery according to some exemplary embodiments, the coating layer may comprise an amorphous carbon-based material.

[0016] In a negative electrode for a secondary battery according to some exemplary embodiments, the coating layer may be formed from pitch.

[0017] In a negative electrode for a secondary battery according to some exemplary embodiments, the first negative electrode active material particle may have a higher hardness than the second negative electrode active material particle.

[0018] In a negative electrode for a secondary battery according to some exemplary embodiments, the ratio of the average particle size of the first negative electrode active material particle to the average particle size of the second negative electrode active material particle may be 0.3 to 0.6.

[0019] In a negative electrode for a secondary battery according to some exemplary embodiments, the second negative electrode active material particle may comprise a graphite-based active material, an amorphous carbon-based material, or a mixture of a graphite-based active material and an amorphous carbon-based material.

[0020] In a negative electrode for a secondary battery according to some exemplary embodiments, the average sphericity (Dn50) of the first negative electrode active material particles may be 0.91 or higher.

[0021] In a negative electrode for a secondary battery according to some exemplary embodiments, the second negative electrode active material particle may include artificial graphite.

[0022] In a negative electrode for a secondary battery according to some exemplary embodiments, the content ratio of the first negative electrode active material to the total weight of the first negative electrode active material and the second negative electrode active material particles may be 60% to 90% by weight.

[0023] A secondary battery according to exemplary embodiments comprises a positive electrode comprising a lithium metal oxide; and a negative electrode for a secondary battery according to exemplary embodiments facing the positive electrode. Effects of the invention

[0024] According to exemplary embodiments, a negative active material can be prepared comprising both a first negative active material particle and a second negative active material particle having a coating layer formed on a core particle. By using the first negative active material particle, which has high hardness including the coating layer, and the second negative active material particle, which has relatively low hardness, together, the rate capability of the negative active material can be improved.

[0025] In addition, since both the first cathode active material particle and the second cathode active material particle, on which a coating layer is formed on the core particle, are included, the rolling characteristics and charging capacity of the cathode active material can be improved.

[0026] According to exemplary embodiments, the mixing ratio of the first cathode active material particles and the second cathode active material particles can be controlled. By controlling the mixing ratio, the press characteristics and high-rate characteristics of the cathode active material can be simultaneously improved. Brief explanation of the drawing

[0027] FIG. 1 is a schematic cross-sectional view showing a negative active material layer according to exemplary embodiments. FIG. 2 is a schematic plan view showing a secondary battery according to exemplary embodiments. FIG. 3 is a schematic cross-sectional view showing a secondary battery according to exemplary embodiments. Specific details for implementing the invention

[0028] Exemplary embodiments of the present invention provide a negative electrode active material for a secondary battery comprising a first negative electrode active material particle in the form of a single particle including a core particle and a coating layer formed on the surface of the core particle, and a second negative electrode active material particle having an average particle size larger than that of the first negative electrode active material particle, wherein the content ratio of the first negative electrode active material is 50% to 100% by weight relative to the total weight of the first negative electrode active material and the second negative electrode active material particle. Additionally, exemplary embodiments provide a secondary battery comprising the negative electrode active material for a secondary battery.

[0029] In exemplary embodiments, the storage characteristics and high rate characteristics of the cathode active material can be improved by including more than 50 weight% of the first cathode active material particles based on the total weight of the first cathode active material and the second cathode active material particles.

[0030] In addition, in a negative electrode active material for a secondary battery according to some exemplary embodiments, the content ratio of the first negative electrode active material relative to the total weight of the first negative electrode active material and the second negative electrode active material particles is preferably 60 weight% or more, and more preferably 70 weight% or more. Likewise, the content ratio of the first negative electrode active material relative to the total weight of the first negative electrode active material and the second negative electrode active material particles is preferably 99 weight% or less, and more preferably 90 weight% or less. By satisfying the above-described numerical ranges for the content ratio of the first negative electrode active material, rate capability, storage capability, and high-rate charging capability can be improved.

[0031] In exemplary embodiments, when the content ratio of the first negative electrode active material is 50 weight% or less, there is a risk that the output characteristics may deteriorate due to a lack of core particles. Conversely, when the content ratio of the first negative electrode active material is 100 weight%, high-pressure pressing conditions are required for sufficient rolling of the first negative electrode active material, and the pore structure of the first negative electrode active material particles may be deformed due to the high-pressure pressing. As a result, a decrease in storage characteristics and rate capability characteristics may occur.

[0033] Hereinafter, embodiments of the present invention will be described in detail with reference to the attached drawings. However, this is merely illustrative and the present invention is not limited to the specific embodiments described illustratively.

[0035] FIG. 1 is a schematic cross-sectional view showing a negative active material layer (120) according to exemplary embodiments. Referring to FIG. 1, it can be seen that the negative active material according to an exemplary embodiment includes a first negative active material particle (50) and a second negative active material particle (60).

[0036] Additionally, the first cathode active material (50) includes a core particle (51) and a coating layer (52) formed on the surface of the core particle (51).

[0037] The core particle (51) may be provided as a particle that provides cathodic activity. For example, the core particle (51) may include one or more of a graphite-based active material and an amorphous carbon-based material. Additionally, the core particle (51) may include a graphite-based material such as artificial graphite and / or natural graphite.

[0038] In some embodiments, the core particle (51) may include artificial graphite. Although artificial graphite may have a smaller capacity than natural graphite, it may have relatively high chemical and thermal stability. Therefore, by employing artificial graphite as the core particle (51), the storage stability or lifespan characteristics of the secondary battery may be improved. Additionally, as described below, a coating layer (52) is formed on the surface of the core particle (51) to improve the hardness of the first negative electrode active material particle (50), and the resistance to electrolyte, high-temperature storage, and rate capability characteristics may be sufficiently improved.

[0039] In some embodiments, the core particle (51) may comprise an amorphous carbonaceous material. Examples of amorphous carbonaceous materials may be carbonaceous materials derived from any one selected from the group consisting of glucose, fructose, galactose, maltose, lactose, sucrose, phenolic resin, naphthalene resin, polyvinyl alcohol resin, urethane resin, polyimide resin, furan resin, cellulose resin, epoxy resin, polystyrene resin, resorcinol resin, phloroglucinol resin, coal pitch, petroleum pitch, tar, and low molecular weight heavy oil, or a mixture of two or more of these.

[0040] In one embodiment, the core particle (51) may include the graphite-based active material, the amorphous carbon-based material, or a mixture of the graphite-based active material and the amorphous carbon-based material.

[0042] The average particle size (D50) of the core particles (51) may be about 1 to 11 μm. D 50 represents the particle diameter at a volume fraction of 50% in the cumulative particle size distribution. Preferably, the average particle size (D) of the core particle (51) 50 ) can be about 4 to 10 μm. By satisfying the above-described numerical range, rolling characteristics and capacitance characteristics can be sufficiently improved when mixed with the second cathode active material.

[0043] The coating layer (52) may be formed on at least a portion of the surface of the core particle (51). In some embodiments, the outer surface of the core particle (51) may be substantially entirely covered by the coating layer (52). Additionally, the coating layer may be formed from an amorphous carbon-based material.

[0044] In some embodiments, the coating layer (52) may be formed from pitch. Examples of the pitch described above may include coal-based pitch, mesophase pitch, petroleum-based pitch, etc. The coating layer (52) formed from pitch may include a material selected from pitch carbide, mesophase pitch carbide, soft carbon, hard carbon, and combinations thereof.

[0046] For example, the thickness of the coating layer (52) may be about 0.001 to 1 μm, preferably 0.001 to 0.1 μm, and more preferably 0.001 to 0.05 μm. By satisfying the above-described numerical range, the destruction of the first cathode active material particles (50) during rolling is limited, so that the high rate characteristics and capacitance characteristics of the core particles (51) can be preserved even after rolling. As a result, the high rate characteristics and capacitance characteristics of the cathode active material including the first cathode active material particles (50) containing the coating layer (52) can be improved.

[0047] In some embodiments, the content ratio of the coating layer (52) to 100 parts by weight of the first negative electrode active material particle (50) may be 0.5 to 3. By satisfying the above-described numerical range, high-temperature storage stability and thermal stability derived from the core particle (51) can be secured without compromising the rate capability of the first negative electrode active material particle (50).

[0048] As the coating layer (52) covers the core particle (51), side reactions, oxidation, corrosion, cracking, etc. on the surface of the core particle (51) can be reduced or prevented. For example, as the charging and discharging of the secondary battery is repeated, the potential for mechanical and chemical damage to the surface of the core particle (51) can be reduced.

[0049] In addition, the generation of gas due to side reactions between the core particle (51) and the electrolyte can be prevented. According to exemplary embodiments, as the coating layer (52) protects the surface of the core particle (51), chemical damage and side reactions caused by direct contact with the electrolyte can be suppressed.

[0050] Additionally, the coating layer (52) may also mitigate the expansion of the core particles (51). As a result, swelling of the core particles (51) and the occurrence of cracks within the particles due to expansion during repeated charging and discharging can also be suppressed.

[0051] In addition, in some exemplary negative electrode active materials, the degree of sphericity of the first negative electrode active material particle (50) may be 0.90 or higher, and preferably 0.91 or higher. By satisfying the above numerical range for the degree of sphericity of the first negative electrode active material particle (50), the uniformity of the coating layer can be improved and the hardness of the first negative electrode active material particle can be improved. As a result, regardless of the pellet density of the negative electrode active material, stress caused by pressure can be effectively dispersed by the first negative electrode active material particle, and the high-rate characteristics and storage characteristics of the negative electrode active material can be further improved.

[0052] The degree of sphericity can be inferred from the aspect ratio of the short axis to the long axis of the first cathode active material particle (50). Additionally, the degree of sphericity can be measured using a particle shape analyzer. For example, the cumulative distribution of the degree of sphericity of the particles to be measured can be derived using a particle shape analyzer, and the degree of sphericity of the particle corresponding to a distribution ratio of 50% from the particles with a high degree of sphericity can be determined as the degree of sphericity of the first particle.

[0053] The second cathode active material particle (60) may include a graphite-based material or an amorphous carbon-based material as described above. Additionally, the graphite-based material described above may include artificial graphite and / or natural graphite, etc.

[0054] Additionally, the shape of the second negative active material particle (60) may be spherical, flake-shaped, amorphous, plate-shaped, rod-shaped, polyhedral, or a mixture thereof. Furthermore, since rolling characteristics and capacitance characteristics can be significantly improved by mixing with the first negative active material particle (50) containing the coating layer (52), it is preferable that the shape of the second negative active material particle (60) be spherical.

[0055] Additionally, the second cathode active material particle (60) may be in the form of a single particle or in the form of an assembly in which two or more single particles are assembled. In order for two or more single particles to be assembled, the second cathode active material particle (60) in the form of an assembly may further include a binder derived from pitch.

[0056] In addition, in some embodiments, the average particle size of the second negative active material particle (60) may be 14 to 18 μm. For example, by satisfying the numerical range described above, the compatibility with the first negative active material particle can be improved, and sufficient pellet density can be achieved even after rolling due to the buffering action of the second negative active material particle.

[0057] Additionally, in some embodiments, the hardness of the first cathode active material particle (50) may be higher than the hardness of the second cathode active material particle (60). The hardness of the first cathode active material particle (50) may be improved by forming a coating layer (52) on the surface of the core particle (51). Since the hardness of the first cathode active material particle (50) is higher than the hardness of the second cathode active material particle (60), the destruction of the first cathode active material particle (50) by rolling is limited, and the output characteristics and capacitance characteristics of the core particle (51) can be maintained even after rolling of the cathode active material.

[0059] In addition, it is preferable that the average particle size of the second cathode active material particle (60) is larger than the average particle size of the first cathode active material particle (50) on which the coating layer (52) is formed on the surface. By satisfying the above conditions, the pellet density of the cathode active material can be significantly improved even after rolling.

[0060] In some embodiments, the ratio of the average particle size of the first cathode active material particle (50) to the average particle size of the second cathode active material particle (60) may be 0.3 to 0.6.

[0061] In some exemplary embodiments, the ratio of the average particle size of the first cathode active material particles (50) satisfies the numerical range described above, so that the pressure during rolling can be appropriately buffered by the second cathode active material particles, the packing of the first cathode active material can be appropriately achieved, and at the same time, the pores formed between the first cathode active material particles and the second cathode active material particles are not excessively blocked, so that the pellet density and output characteristics of the cathode active material can be improved in balance. As a result, the storage characteristics and rate capability characteristics of the cathode active material can be improved.

[0063] Additionally, pellet density can be used as an indicator of the hardness of the particles to be measured. For example, the pellet density of the first cathode active material particles can be used as an indicator of the hardness of the first cathode active material particles, and the pellet density of the second cathode active material particles can be used as an indicator of the hardness of the second cathode active material particles. In exemplary embodiments, a higher pellet density can be interpreted as indicating lower hardness of the particles (samples) to be measured.

[0064] Pellet density can be measured using a density meter. Prior to using the density meter, a process of compressing the sample to be measured into a pellet shape may be performed.

[0065] In some exemplary embodiments, the pellet density of the first cathode active material particle is preferably 1.6 g / cc (4 kN) or less. Additionally, the pellet density of the second cathode active material particle mixed with the first cathode active material particle is preferably greater than 1.6 g / cc (4 kN).

[0066] By satisfying the aforementioned numerical ranges for the pellet density of the first cathode active material particles and the pellet density of the second cathode active material particles, the second cathode active material particles, which have a relatively large average particle size, can perform a buffering function during the rolling of the electrode, and the output characteristics of the first cathode active material particles, which have a relatively small average particle size and high hardness, can be maintained even after rolling. As a result, the capacitance characteristics and high-rate characteristics of the electrode can be improved and maintained even after rolling.

[0068] According to exemplary embodiments, the negative electrode active material can be manufactured according to the method and process described below.

[0069] For example, a core particle (51) containing the graphite-based active material described above may be prepared. Subsequently, a coating layer (52) may be formed on the core particle (51).

[0070] The coating layer (52) can be formed by a dry or wet coating method. For example, when the coating layer (52) is formed through a wet coating method, pitch containing pitch particles and core particles (51) can be mixed and stirred. Afterward, pitch particles can be uniformly adsorbed onto the surface of the core particles (51) through heat treatment.

[0071] After a coating layer (52) is formed on the first cathode active material particle (50), the first cathode active material particle (50) and the second cathode active material particle (60) can be mixed. By mixing, physical contact between the first cathode active material particles (50) can be increased. Additionally, by mixing, physical contact between the first cathode active material particle (50) and the second cathode active material particle (60) can be increased. Stirring can be appropriately performed so that the first cathode active material particle (50) and the second cathode active material particle (60) are uniformly mixed.

[0072] Additionally, the first cathode active material particles (50) and the second cathode active material particles (60) that have been appropriately stirred may be applied onto a cathode current collector, and the applied first cathode active material particles (50) and the second cathode active material particles (60) may be rolled. Rolling may be performed by a conventional method such as a roll press.

[0074] FIGS. 2 and FIGS. 3 are schematic plan and cross-sectional views, respectively, showing a secondary battery according to exemplary embodiments. For example, FIG. 3 is a cross-sectional view taken along the thickness direction of the lithium secondary battery along the line II' shown in FIG. 2.

[0075] Referring to FIGS. 2 and FIGS. 3, the secondary battery may be provided as a lithium secondary battery. According to exemplary embodiments, the secondary battery may include an electrode assembly (150) and a case (160) that accommodates the electrode assembly (150). The electrode assembly (150) may include a positive electrode (100), a negative electrode (130), and a separator (140).

[0076] The positive electrode (100) may include a positive electrode current collector (105) and a positive electrode active material layer (110) formed on at least one surface of the positive electrode current collector (105). According to exemplary embodiments, the positive electrode active material layer (110) may be formed on both surfaces (e.g., an upper surface and a lower surface) of the positive electrode current collector (105). For example, the positive electrode active material layer (110) may be coated on the upper surface and the lower surface of the positive electrode current collector (105), respectively, and may be coated directly on the surface of the positive electrode current collector (105).

[0077] The positive current collector (105) may include, for example, stainless steel, nickel, aluminum, titanium, copper, or an alloy thereof, and preferably may include aluminum or an aluminum alloy.

[0078] The positive active material layer (110) comprises a lithium metal oxide as the positive active material, and according to exemplary embodiments, may comprise a lithium (Li)-nickel (Ni)-based oxide.

[0079] In some embodiments, the lithium metal oxide included in the positive active material layer (110) may be represented by the following chemical formula 1.

[0080] [Chemical Formula 1]

[0081] Li 1+a Ni 1-(x+y) Co x M y O2

[0082] In the above chemical formula 1, -0.05≤α≤0.15, 0.01≤x≤0.2, 0≤y≤0.2, and M may be one or more elements selected from the group consisting of Mg, Sr, Ba, B, Al, Si, Mn, Ti, Zr, and W. In one embodiment, 0.01≤x≤0.20 and 0.01≤y≤0.15 may be present.

[0083] Preferably, in Formula 1, M may be manganese (Mn). In this case, a nickel-cobalt-manganese (NCM) lithium oxide may be used as the positive electrode active material.

[0084] For example, nickel (Ni) may be provided as a metal associated with the capacity of a lithium secondary battery. While a higher nickel content may improve the capacity of the lithium secondary battery, an excessive increase in nickel content may reduce lifespan and be disadvantageous in terms of mechanical and electrical stability. For example, cobalt (Co) may be a metal associated with the conductivity, resistance, and output of the lithium secondary battery. In one embodiment, M includes manganese (Mn), and Mn may be provided as a metal associated with the mechanical and electrical stability of the lithium secondary battery.

[0085] Through the interaction of nickel, cobalt, and manganese described above, the capacity, output, low resistance, and lifespan stability of the positive active material layer (110) can be improved together.

[0086] For example, a slurry can be prepared by mixing and stirring a positive active material with a binder, a conductive material and / or a dispersant, etc., in a solvent. After coating the slurry onto a positive current collector (105), a positive active material layer (110) can be formed by compressing and drying.

[0087] The above binder may include, for example, organic binders such as vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidenefluoride (PVDF), polyacrylonitrile, and polymethylmethacrylate, or water-based binders such as styrene-butadiene rubber (SBR), and may be used together with a thickener such as carboxymethyl cellulose (CMC).

[0088] For example, a PVDF-based binder can be used as a binder for forming the positive electrode. In this case, the amount of binder for forming the positive electrode active material layer (110) can be reduced, and the amount of the positive electrode active material or lithium metal oxide particles can be relatively increased, thereby improving the output and capacity of the secondary battery.

[0089] The above conductive material may be included to promote electron transfer between active material particles. For example, the conductive material may include carbon-based conductive materials such as graphite, carbon black, graphene, carbon nanotubes, etc., and / or metal-based conductive materials such as perovskite materials such as tin, tin oxide, titanium oxide, LaSrCoO3, LaSrMnO3, etc.

[0090] In some embodiments, the electrode density of the anode (100) may be 3.0 to 3.9 g / cc, and preferably 3.2 to 3.8 g / cc.

[0091] The negative electrode (130) may include a negative current collector (125) and a negative active material layer (120) formed on at least one surface of the negative current collector (125). According to exemplary embodiments, the negative active material layer (120) may be formed on both sides (e.g., the upper surface and the lower surface) of the negative current collector (125). The negative active material layer (120) may be coated on the upper surface and the lower surface of the negative current collector (125), respectively. For example, the negative active material layer (120) may be in direct contact with the surface of the negative current collector (125).

[0092] The negative current collector (125) may include gold, stainless steel, nickel, aluminum, titanium, copper, or an alloy thereof, and preferably may include copper or a copper alloy.

[0093] According to exemplary embodiments, the negative active material layer (120) may include a negative active material (50) according to the exemplary embodiments described above. For example, the negative active material (50) may be included in an amount of 80 to 99 weight percent with respect to the total weight of the negative active material layer (120). Preferably, the negative active material may be included in an amount of 90 to 98 weight percent with respect to the total weight of the negative active material layer (120).

[0094] For example, a cathode active material (50) can be mixed and stirred with a binder, a conductive material and / or a dispersant, etc. in a solvent to prepare a cathode slurry. After applying (coating) the cathode slurry onto a cathode current collector (125), a cathode active material layer (120) can be formed by compressing (rolling) and drying.

[0095] Materials substantially identical or similar to those used for forming the anode (100) may be used as the binder and conductive material. In some embodiments, the binder for forming the cathode (130) may include, for example, styrene-butadiene rubber (SBR) or an acrylic binder for compatibility with a graphite-based active material, and may be used together with a thickener such as carboxymethyl cellulose (CMC).

[0096] In exemplary embodiments, the density of the negative active material layer (120) may be 1.4 to 1.9 g / cc.

[0097] In some embodiments, the area (e.g., the contact area with the separator (140)) and / or volume of the negative electrode (130) may be larger than that of the positive electrode (100). Accordingly, lithium ions generated from the positive electrode (100) may move smoothly to the negative electrode (130) without precipitating, for example, in the middle, thereby further improving output and capacity characteristics.

[0098] A separator (140) may be interposed between the anode (100) and the cathode (130). The separator (140) may include a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, an ethylene / methacrylate copolymer, etc. The separator may also include a nonwoven fabric formed of high-melting-point glass fibers, polyethylene terephthalate fibers, etc.

[0099] The separator (140) extends in the second direction between the positive electrode (100) and the negative electrode (130) and can be folded and wound along the thickness direction of the lithium secondary battery. Accordingly, a plurality of positive electrodes (100) and negative electrodes (130) can be stacked in the thickness direction through the separator (140).

[0100] According to exemplary embodiments, an electrode cell is defined by an anode (100), a cathode (130), and a separator (140), and a plurality of electrode cells may be stacked to form, for example, an electrode assembly (150) in the form of a jelly roll. For example, the electrode assembly (150) may be formed by winding, laminating, folding, etc., of the separator (140).

[0101] The electrode assembly (150) is housed within a case (160), and an electrolyte may be injected into the case (160) together. The case (160) may include, for example, a pouch, a can, etc.

[0102] According to exemplary embodiments, a non-aqueous electrolyte may be used as the electrolyte.

[0103] The non-aqueous electrolyte comprises a lithium salt as an electrolyte and an organic solvent, and the lithium salt is, for example, Li + X - It is expressed as and the anion (X) of the above lithium salt - As F - , Cl- , Br - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - Examples of the back can be given.

[0104] Examples of the above organic solvents may include propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethylmethyl carbonate (EMC), methylpropyl carbonate, dipropyl carbonate, dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, vinylene carbonate, sulfolane, gamma-butyrolactone, propylene sulfite, and tetrahydrofuran. These may be used individually or in combination of two or more.

[0105] As illustrated in FIG. 2, electrode tabs (positive tabs and negative tabs) may protrude from the positive current collector (105) and negative current collector (125) belonging to each electrode cell, respectively, and extend to one side of the outer case (160). The electrode tabs may be fused together with the one side of the outer case (160) and connected to electrode leads (positive lead (107) and negative lead (127)) that extend or are exposed to the outside of the outer case (160).

[0106] In FIG. 2, the positive lead (107) and the negative lead (127) are shown as being formed on the same side of the lithium secondary battery or outer case (160), but they may be formed on opposite sides.

[0107] For example, the positive lead (107) may be formed on one side of the outer case (160), and the negative lead (127) may be formed on the other side of the outer case (160).

[0108] Lithium secondary batteries can be manufactured in various forms, such as cylindrical, prismatic, pouch, or coin types using cans, for example.

[0110] Hereinafter, experimental examples including specific embodiments and comparative examples are presented to aid in understanding the present invention; however, these are merely illustrative of the invention and do not limit the appended claims. It is obvious to those skilled in the art that various changes and modifications to the embodiments are possible within the scope and spirit of the present invention, and that such variations and modifications fall within the scope of the appended claims.

[0112] Example 1

[0113] 100 g of artificial graphite with an average particle size (D50) of about 7 μm and 3 g of petroleum-based pitch were put into a mixer (manufactured by Inoue) and mixed for 30 minutes at a stirring speed of 20 Hz, and then calcined at 1000°C to prepare a first cathode active material particle with a coating layer formed on its surface.

[0114] The content ratio (coating amount) of the coating layer was 1.5% relative to 100 parts by weight of the total first cathode active material particles. The median value of the coating thickness estimated from the coating amount was approximately 10 nm. When the pressurization condition was 4 kN, the density of the pellet containing only the first cathode active material particles was found to be 1.59 g / cc.

[0115] In addition, 100g of artificial graphite with an average particle size (D50) of about 12 μm was prepared as the second cathode active material particle. When the pressurization condition was 4 kN, the density of the pellet containing only the second cathode active material particle was found to be 1.69 g / cc.

[0116] 60 parts by weight of the prepared first cathode active material particles and 40 parts by weight of the second cathode active material particles were put into a mixer and mixed for 10 minutes at a stirring speed of 5 Hz to prepare the cathode active material.

[0117] As described above, a cathode slurry was prepared by mixing the manufactured cathode active material, CMC, and SBR in a weight ratio of 97.3:1.2:1.5. After coating the cathode slurry onto a Cu foil, drying and rolling were performed to produce a cathode with a rolling density of 1.70 g / cc.

[0118] A coin cell-type secondary battery was manufactured using a Li foil as the counter electrode and an electrolyte containing 1M LiPF6 and an EC:EMC=3:7 mixed solvent.

[0120] Examples 2 to 4

[0121] Prepared in the same manner as Example 1, but with different amounts of the first cathode active material and the second cathode active material as shown in Table 1 below.

[0122] The rolled density of each cathode was 1.70 g / cc, which was the same as the cathode of Example 1.

[0124] Example 5

[0125] The procedure was carried out in the same manner as in Example 1, but 4g of petroleum-based pitch was mixed with 100g of artificial graphite having an average particle size (D50) of about 9 μm and calcined at 1000°C to prepare a first negative active material particle with a coating layer formed on its surface.

[0126] The content ratio of the coating layer (coating amount) was 2% relative to 100 parts by weight of the total first cathode active material particles. The median value of the coating thickness estimated from the coating amount was approximately 15 nm. When the pressurization condition was 4 kN, the pellet density containing only the first cathode active material particles was found to be 1.59 g / cc.

[0127] In addition, 100g of artificial graphite with an average particle size (D50) of about 18 μm was prepared as the second cathode active material particle. When the pressurization condition was 4 kN, the density of the pellet containing only the second cathode active material particle was found to be 1.69 g / cc.

[0128] The rolled density of the cathode was 1.70 g / cc, which was the same as the cathode of Example 1.

[0130] Example 6

[0131] The procedure was carried out in the same manner as in Example 1, but 5g of petroleum-based pitch was mixed with 100g of artificial graphite having an average particle size (D50) of about 9 μm and calcined at 1000°C to prepare a first negative active material particle with a coating layer formed on its surface.

[0132] The content ratio of the coating layer (coating amount) was 2% relative to 100 parts by weight of the total first cathode active material particles. The median value of the coating thickness estimated from the coating amount was approximately 18 nm. When the pressurization condition was 4 kN, the pellet density containing only the first cathode active material particles was found to be 1.55 g / cc.

[0133] In addition, 100g of artificial graphite with an average particle size (D50) of about 18 μm was prepared as the second cathode active material particle. When the pressurization condition was 4 kN, the density of the pellet containing only the second cathode active material particle was found to be 1.66 g / cc.

[0134] The rolled density of the cathode was 1.70 g / cc, which was the same as the cathode of Example 1.

[0136] Comparative Example 1 and Comparative Example 2

[0137] It was prepared in the same manner as in Example 1, but the content of the first cathode active material and the second cathode active material was varied as shown in Table 1 below. The rolled density of each cathode was 1.70 g / cc, which was the same as the cathode of Example 1.

[0139] Comparative Examples 3 and 4

[0140] The same artificial graphite as in Example 5 was used, but a coating layer was not formed on the surface of the first cathode active material particle. Conversely, a coating layer was formed on the surface of the second cathode active material particle using petroleum-based pitch. The composition and measurement results of Comparative Examples 3 and 4 are shown in Table 2 below. The rolled density of each cathode was 1.70 g / cc, which was the same as that of the cathode in Example 1.

[0142] Experimental Example

[0143] (1) High-rate filling ability evaluation

[0144] After repeating charge and discharge cycles for 10 cycles at a c-rate of 2.0 C charge / 0.33 C discharge in a chamber maintained at 25℃, the retention capacity ratio was measured. The evaluation results are shown in Table 2 below. The evaluation results are shown in Tables 1 and 2 below.

[0146] Evaluation criteria Content ratio * (mass%) Pellet density ** (g / cc, 4 kN) High charging rate *** Examples 1 60 1.67 81 2 70 1.74 85 3 80 1.64 83 4 90 1.63 83 Comparative example 1 50 1.60 75 2 100 1.59 71

[0148] * Refers to the weight of the first cathode active material particle among a total of 100 parts by weight of the sum of the first cathode active material particle and the second cathode active material particle.

[0149] ** This is the pellet density of the cathode active material obtained by mixing the first cathode active material particles and the second cathode active material particles according to the above content ratio.

[0150] *** The value indicated on the high-rate filling indicator represents the residual capacity ratio, in %, and is rounded down to the first decimal place.

[0152] (2) Evaluation of pellet density

[0153] Pellet density refers to the density of the first cathode active material particles and the second cathode active material particles, which are the samples. By measuring the pellet density, the hardness of the first cathode active material particles and the second cathode active material particles can be estimated. Typically, the value of pellet density may be measured to be greater than the value of rolled density, which refers to the density of the cathode after rolling.

[0154] To measure pellet density, the sample is compressed into a pellet shape of a specific size by applying a force of 4 kN. The pellet density of the compressed sample was determined by measuring the change in volume of the pellet at this time. The specific method for measuring pellet density is as follows.

[0155] a) Measure the height (H1) of an empty pelletizer (diameter 13 mm) (unit is mm). b) Load approximately 2 ± 0.1 g (W) of the sample into the sample inlet of the pelletizer. c) Place the pelletizer on the center of a manual type presser. d) Pressurize the sample until the applied pressure reaches 4 kN. e) Pressurize for 10 seconds and measure the height of the pelletizer (H2, unit is mm).

[0156] The formula for calculating pellet density based on the values ​​obtained from the above measurement method is as follows: Equation 1.

[0157] [Equation 1]

[0158] Pellet density = W / [π×(20 mm / 2) 2 ×(H2-H1) / 1000]

[0160] (3) Evaluation of sphericity

[0161] For Example 5 and Comparative Examples 3 and 4, the degree of sphericity was measured and the high-rate filling capability was evaluated. The degree of sphericity of the first cathode active material particles included in Example 5 and Comparative Examples 3 and 4 was measured using a particle shape analyzer (Malvern, Morphologi 4).

[0162] Specifically, after deriving the cumulative distribution of the sphericity of the first cathode active material particles using a particle shape analyzer, the sphericity (Dn) corresponding to a distribution ratio of 50% starting from particles with high sphericity. 50 ) was determined as the degree of sphericity of the first cathode active material particle.

[0164] Evaluation criteria Content ratio * (mass%) Pellet density ** (g / cc, 4 kN) Sphericity *** (Dn50) High charging rate + Examples 5 70 1.72 0.914 85 6 70 1.62 0.919 87 Comparative example 3 70 1.66 0.902 78 4 70 1.65 0.899 71

[0166] * Refers to the weight of the first cathode active material particle among a total of 100 parts by weight of the sum of the first cathode active material particle and the second cathode active material particle.

[0167] ** This is the pellet density of the cathode active material obtained by mixing the first cathode active material particles and the second cathode active material particles according to the above content ratio.

[0168] *** This is the degree of sphericity of the first cathode active material particle.

[0169] + The value indicated in the high-rate filling indicator represents the residual capacity ratio, in %, and all decimal places after the first decimal place are truncated.

[0171] Referring to Tables 1 and 2 above, it can be confirmed that all negative electrode active materials according to the examples have superior high-rate charging performance compared to the negative electrode active materials of the comparative examples. For example, the negative electrode active material according to the examples had a residual capacity exceeding 80% even after repeated high-rate charging.

[0172] In the case of Example 6, the pellet density was found to be 1.62 g / cc, but the degree of sphericity was found to be high at 0.919, and the high-rate filling performance was found to be the best.

[0173] Conversely, the negative electrode active material according to the comparative example was found to have insufficient high-rate charging capability. For example, the negative electrode active material according to the comparative example provided less than 80% of the residual capacity when high-rate charging was repeated.

[0174] The negative electrode active material of Comparative Example 1 was found to have insufficient high-rate characteristics due to the insufficient content of the first negative electrode active material. In addition, the negative electrode active material of Comparative Example 2 was found to have degraded high-rate characteristics due to the destruction of the second negative electrode active material and / or blockage of the internal pores of the negative electrode active material during the high-pressure pressing process to achieve a rolling density of 1.7 g / cc.

[0175] Meanwhile, in the case of Comparative Examples 3 and 4, a second cathode active material with relatively high hardness was used, and it was found that the rolling density exceeded 1.6 g / cc. However, it was found that the high-rate characteristics deteriorated during the high-pressure pressing process because the degree of sphericity of the first cathode active material was insufficient. Explanation of the symbols

[0177] 50: First cathode active material particle 51: Core particle 52: Coating layer 60: Second cathode active material particle 100: Anode 105: Anode current collector 110: Positive electrode active material layer 120: Negative electrode active material layer 125: Cathode current collector 130: Cathode 140: Separator 150: Electrode assembly 160: Case

Claims

Claim 1 A negative electrode for a secondary battery comprising: a first negative active material particle in the form of a single particle including a core particle and a coating layer formed on the surface of the core particle; and a second negative active material particle having an average particle size larger than that of the first negative active material particle, wherein the content ratio of the first negative active material in the total weight of the first negative active material particle and the second negative active material particle is greater than 50 weight% and less than 100 weight%, and the core particle comprises artificial graphite. Claim 2 A negative electrode for a secondary battery according to claim 1, wherein the core particles comprise a graphite-based active material, an amorphous carbon-based material, or a mixture of a graphite-based active material and an amorphous carbon-based material. Claim 3 delete Claim 4 A negative electrode for a secondary battery according to claim 1, wherein the coating layer comprises an amorphous carbon-based material. Claim 5 A negative electrode for a secondary battery according to claim 1, wherein the coating layer is formed from pitch. Claim 6 A negative electrode for a secondary battery according to claim 1, wherein the first negative electrode active material particle has a higher hardness than the second negative electrode active material particle. Claim 7 A negative electrode for a secondary battery according to claim 1, wherein the ratio of the average particle size of the first negative electrode active material particle to the average particle size of the second negative electrode active material particle is 0.3 to 0.

6. Claim 8 A negative electrode for a secondary battery according to claim 1, wherein the second negative electrode active material particle comprises a graphite-based active material, an amorphous carbon-based material, or a mixture of a graphite-based active material and an amorphous carbon-based material. Claim 9 A negative electrode for a secondary battery according to claim 1, wherein the average sphericity (Dn50) of the first negative electrode active material particles is 0.91 or higher. Claim 10 A negative electrode for a secondary battery according to claim 1, wherein the second negative electrode active material particle comprises artificial graphite. Claim 11 A negative electrode for a secondary battery according to claim 1, wherein the content ratio of the first negative electrode active material to the total weight of the first negative electrode active material and the second negative electrode active material particles is 60% to 90% by weight. Claim 12 A secondary battery comprising an anode comprising a lithium metal oxide; and a negative electrode for a secondary battery according to claim 1, facing the anode.

Citation Information

Patent Citations

  • Anode with improved swelling phenomenon and Lithium secondary battery comprising the anode

    KR1020180028797A

  • Negative electrode for non-aqueous secondary battery and non-aqueous secondary battery using the negative electrode

    US20180083270A1

  • Anode active material and secondary battery comprising the same

    KR1020170093754A

  • Negative electrode and lithium secondary battery comprising the negative electrode

    KR1020200073801A

  • Negative active material for rechargeable lithium battery, negative electrode for rechargeable lithium battery including same, and rechargeable lithium battery including same

    KR1020210053061A